GERAKAN SADAR HUKUM MENGENAI FAKE NEWS DAN AKIBAT HUKUMNYA - Kadarudin; Marthen Napang; Iin Karita Sakharina; Girillano Reyhan Uno; Aviel Paelongan Dase (The Juris, 2022)
Various fake news appears in the mainstream media and become a phenomenon that must be handled with a smart and wise attitude by its users, especially among junior high school students. The spread of fake news can occur massively due to the inaccuracy of students in receiving the information that is circulating. Something considered "viral" will easily affect existing rules, norms, and culture. Open spaces are easier to access as targets for the spread of fake news which can trigger disintegrative actions for the nation if they are not based on adequate references.